Consciousness depths and psychological defence mechanisms - Spytska, Liana (Revista Interdisciplinar de Ciência Aplicada, 2025)
The study of the depth of consciousness and psychological defence mechanisms is particularly relevant nowadays, as it allows us to better understand how stressful conditions affect people, shape their behaviour, and affect their mental health. The study aims to examine in detail the peculiarities of human consciousness and its changes in the context of activation of psychological defence mechanisms. The method of analysis, systematisation and survey was used in the study. As a result of the scientific research, the concept of consciousness and its key components in the context of the human psyche were considered. As a result of the work, the peculiarities of brain activity, which is a central component of the mechanisms of consciousness, were studied and highlighted. In addition, the study revealed details of the evolutionary development of mental defence mechanisms. This study examines the impact of stressors on the activation and modification of mental defence mechanisms and analyses both constructive and destructive mental defence mechanisms. The research shows that psychological defence mechanisms are dynamic structures that can change depending on specific conditions and circumstances. The paper surveyed respondents on their understanding of the phenomenon of depth of consciousness and psychological defence mechanisms. The results of the survey indicate a high level of education and awareness of the respondents regarding the phenomenon of consciousness and mechanisms of mental protection. In the course of analysing the survey results, it was found that 98% of respondents expressed a positive attitude towards the need for in-depth education in the context of consciousness, indicating a high level of motivation for academic and psychological self-improvement. Within the same sample, 80% of participants reflected on psychological counselling as an effective mechanism for analysing and adapting psychological defence mechanisms.